Combustion synthesis of calcium aluminates - Fumo, D.A. (1996)
Commercial calcium aluminate cements for refractory use are known to contain various phases, the hydration behavior of which is interdependent and not fully understood. Hydration studies normally require that pure oxides be synthesized. Solid-state synthesis of single aluminates requires high temperatures and full conversion is not guaranteed. Moreover, it is difficult to obtain a compositionally homogeneous product with this method. The present work discusses a straightforward combustion synthesis technique to prepare submicron calcium aluminates using the corresponding metal nitrates-urea mixtures, at low temperature and short reaction times. The effect of the ratio oxidizer/fuel in the redox mixture was investigated, namely, to find out if urea contents below stoichiometry were enough to trigger the explosive combustion of the fuel and the subsequent decomposition of the salts, and how that ratio affected the phase formation and the characteristics, e.g., morphology and grain size, of the powder produced.